2005
DOI: 10.1093/ajcn/81.4.829
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of selenium supplements in a low-selenium area of China

Abstract: Full expression of selenoprotein P requires a greater selenium intake than does full expression of plasma glutathione peroxidase. This suggests that selenoprotein P is a better indicator of selenium nutritional status than is glutathione peroxidase and that the recommended dietary allowance of selenium, which was set with the use of glutathione peroxidase as the index of selenium status, should be revised. Selenium as selenomethionine had nearly twice the bioavailability of selenium as selenite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
186
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(200 citation statements)
references
References 13 publications
7
186
0
6
Order By: Relevance
“…Since it has been recently shown that the two serum selenoproteins (Sel P and GPX 3) are maximally expressed at different levels of supplemental selenium [19], we wanted to determine if two selenoproteins were induced to the same extent at the same level of selenium supplementation in prostate cells. To that end, the samples used to examine GPX1 levels were also examined for GPX4 expression via Selenoproteins in prostate cells 944 npg mentation increased GPX2 levels only by about a factor of ~2.…”
Section: Gpx4 Induction Is Similar To That Of Gpx1mentioning
confidence: 99%
“…Since it has been recently shown that the two serum selenoproteins (Sel P and GPX 3) are maximally expressed at different levels of supplemental selenium [19], we wanted to determine if two selenoproteins were induced to the same extent at the same level of selenium supplementation in prostate cells. To that end, the samples used to examine GPX1 levels were also examined for GPX4 expression via Selenoproteins in prostate cells 944 npg mentation increased GPX2 levels only by about a factor of ~2.…”
Section: Gpx4 Induction Is Similar To That Of Gpx1mentioning
confidence: 99%
“…Se has been studied in relation to this neoplasia due to its possible preventive effects on DNA damage. The chemical form of Se and the dose are determinants of its biological activities as an essential nutrient, chemopreventive agent, or toxicant (33,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…The normative individual and population requirements for Se are based on the results from the United States, and are 27 and 39 mg/day, respectively (WHO, 1996). It has also been suggested that selenoprotein P is a better indicator of selenium nutritional status than glutathione peroxidase, and thus the recommended dietary allowance of selenium may need to be greater than that of World Health Organization, because full expression of selenoprotein P requires a greater selenium intake than does full expression of plasma glutathione peroxidase (Xia et al, 2005).…”
Section: Discussionmentioning
confidence: 99%